Reservation for Economically Weaker Section Children in Unaided-Private Schools: Policy and Practice - Yagnamurthy, Sreekanth (EDUCARE, 2013)
ABSTRACT: The paper examines the assertion of reservation of seats to economically weaker section (EWS) children in unaided-private schools at state level in consequence of an agreement between a land granting authority and unaided private educational institutions. It involved considerable amount of negotiation and initiative of several stakeholders such as non-governmental organization (NGO), judiciary, and government with the private educational institutions to secure reservation. The author, as a special invitee to the state level committee which was appointed to look into modalities of EWS reservation, has recorded the deliberations which highlight the view points of the representatives of private schools and NGO. Further, interviews with the few parents of EWS children provide information on some of the ground realities. With the inclusion of 25 per cent reservation for EWS children under Right to Education Act 2009 at national level, the issues raised by the stakeholders at state level carry significance in implementation. It is concluded that in addition to effective measures for implementation of reservation for EWS children, it is necessary to improve the functioning of government schools to check excessive exodus of children to unaided-private schools.KEY WORDS: Unaided private schools, economically weaker section, elementary education, equity in education, and social inclusion.About the Author: Dr. Sreekanth Yagnamurthy is an Associate Professor Â at the National University of Educational Planning and Administration, 17-B, Sri Aurobindo Marg, New Delhi 110016, India. He can be contacted via his e-mail at: syagnamurthy@yahoo.com and sreekanth@nuepa.orgHow to cite this article? Yagnamurthy, Sreekanth. (2013). âReservation for Economically Weaker Section Children in Unaided-Private Schools: Policy and Practiceâ in EDUCARE: International Journal for Educational Studies, Vol.5(2) February, pp.201-222. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 5, 2012); Revised (January 8, 2013); and Published (February 17, 2013).Â Â